Newly Identified Electrically Coupled Neurons Support Development of the Drosophila Giant Fiber Model Circuit - Kennedy, Tyler (eNeuro, 2018)
The Drosophila giant fiber (GF) escape circuit is an extensively studied model for neuron connectivity and function. Researchers have long taken advantage of the simple linear neuronal pathway, which begins at peripheral sensory modalities, travels through the central GF interneuron (GFI) to motor neurons, and terminates on wing/leg muscles. This circuit is more complex than it seems, however, as there exists a complex web of coupled neurons connected to the GFI that widely innervates the thoracic ganglion. Here, we define four new neuron clusters dye coupled to the central GFI, which we name GF coupled (GFC) 1–4. We identify new transgenic Gal4 drivers that express specifically in these neurons, and map both neuronal architecture and synaptic polarity. GFC1–4 share a central site of GFI connectivity, the inframedial bridge, where the neurons each form electrical synapses. Targeted apoptotic ablation of GFC1 reveals a key role for the proper development of the GF circuit, including the maintenance of GFI connectivity with upstream and downstream synaptic partners. GFC1 ablation frequently results in the loss of one GFI, which is always compensated for by contralateral innervation from a branch of the persisting GFI axon. Overall, this work reveals extensively coupled interconnectivity within the GF circuit, and the requirement of coupled neurons for circuit development. Identification of this large population of electrically coupled neurons in this classic model, and the ability to genetically manipulate these electrically synapsed neurons, expands the GF system capabilities for the nuanced, sophisticated circuit dissection necessary for deeper investigations into brain formation.